Comparison Of The Effectiveness Of Irrigation and Manual Extraction Techniques On The Comfort Level Of Serumen-Impacted Patients Using The Kolcaba Comfort Theory Approach - Yobel, Sosilo (Adi Husada Nursing Journal, 2023)
A buildup of cerumen, or earwax, in the ear canal is one of the most common problems experienced by patients and, if ignored, can cause hearing loss, irritation, and discomfort. Comfort is an integral part of nursing work as a client's basic needs which is the goal of nursing work. The nursing approach to providing comfort to patients is based on Kolcaba's comfort theory. This theory includes comfort in four contexts of comfort, namely: physical, psychospiritual, sociocultural, and environmental. The purpose of this study was to compare irrigation techniques' effectiveness with manual extraction on the comfort level of cerumen-impacted patients using the Kolcaba comfort theory approach. This research is pre-experimental research with a "two independent samples test" approach. The sample was 40 respondents who had impacted cerumen, divided into 20 respondents who underwent ear irrigation and 20 respondents who underwent manual extraction. Analysis to determine differences in comfort levels after intervention using the Mann-Whitney test. Results & Analysis. The Mann-Whitney test showed P value = 0.000 (P <0.05), and there was a difference in the comfort level between irrigation and manual extraction. The action of ear irrigation further increases the respondent's sense of comfort compared to manual extraction, because irrigation is more effective in removing impacted cerumen characterized by clean ears and clearer hearing, and does not cause pain.